2011
DOI: 10.1021/jp106657a
|View full text |Cite
|
Sign up to set email alerts
|

Errors and Error Tolerance in Irreversible Multistep Growth of Nanostructures

Abstract: Error correction is one of the main features allowing self-assembly and other reversible growth processes to create giant, ordered molecular structures at the nanometer scale and above. On the other hand, in irreversible growth processes, such as chemical synthesis, errors (defects) are usually not removable and, as a result, growth is limited to a small number of synthetic steps and formation of relatively small structures. In this work, we develop a general model and theory to describe the behavior of errors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Alkynyl-based monomers have been widely employed for constructing CMP materials. 45,[128][129][130] Here, we mainly summarize four typical coupling shown in Scheme 3. A series of CMP materials have been prepared by using Pd(II)/Cu(I)-catalyzed homocoupling polymerization (route "a" in Scheme 3), such as HCMP-1 (TEB), 131,132 HCMP-2 (DEB), 131 PPN-1 (TEPM), 133 PPN-2 (TKEPA), 133 5 (TEPM).…”
Section: Alkynyl Group-based Couplingmentioning
confidence: 99%
“…Alkynyl-based monomers have been widely employed for constructing CMP materials. 45,[128][129][130] Here, we mainly summarize four typical coupling shown in Scheme 3. A series of CMP materials have been prepared by using Pd(II)/Cu(I)-catalyzed homocoupling polymerization (route "a" in Scheme 3), such as HCMP-1 (TEB), 131,132 HCMP-2 (DEB), 131 PPN-1 (TEPM), 133 PPN-2 (TKEPA), 133 5 (TEPM).…”
Section: Alkynyl Group-based Couplingmentioning
confidence: 99%
“…Despite the vast amount of work so far presented, our perusal of the literature has evidenced that only a few articles discuss the effect of coupling Janus self-assembly with processes or fields (e.g., evaporation, flows, etc.) compared to near-thermodynamics studies; this contrasts sharply with the attention paid toward the self-assembling under various solvent evaporation conditions of mono- or poly-dispersed NPs with homogeneous interactions. Noticeably, the latter studies have shown how a wide set of final aggregation patterns can be induced upon varying specific details such as the evaporation regime or ratio between diffusion and evaporation rates. Thus, coverage patterns such as disks, worm-like aggregates, , networks, ,, , rings ,,, and hexagons, , fingers, ,, linear or bridged wires, stalagmites, , and check or stripe , patterned aggregates have been shown and interpreted with the help of simulation approaches.…”
Section: Introductionmentioning
confidence: 96%
“…However, it is limited by its lack of reversibility and error correction, which often results in reduced overall yield. 1,4 The second method is based on using reversible equilibrium reactions, which by themselves could be inaccurate and could lead to a large number of products. Yet the reversibility of the reaction can cause the majority of the products to be transformed back into the starting materials while leaving only specific stable structures.…”
Section: Introductionmentioning
confidence: 99%
“…The first method involves the synthesis of a structure by using an irreversible sequence of mostly accurate reactions that leads to a target structure. This method is used in the majority of syntheses of organic molecules. However, it is limited by its lack of reversibility and error correction, which often results in reduced overall yield. , The second method is based on using reversible equilibrium reactions, which by themselves could be inaccurate and could lead to a large number of products. Yet the reversibility of the reaction can cause the majority of the products to be transformed back into the starting materials while leaving only specific stable structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation